How accurate channel prediction needs to be for transmit-beamforming with adaptive modulation over Rayleigh MIMO channels?. - Shengli Zhou (IEEE Transactions on wireless communications)
Adaptive modulation improves the system throughput considerably by matching transmitter parameters to time-varying wireless fading channels. Crucial to adaptive modulation is the quality of channel state information at the transmitter. In this paper, we first present a channel predictor based on pilot symbol assisted modulation for multiple-input multiple-output Rayleigh fading channels. We then analyze the impact of the channel prediction error on the bit error rate performance of a transmit-beamformer with adaptive modulation that treats the predicted channels as perfect. Our numerical results reveal the critical value of the normalized prediction error, below which the predicted channels can be treated as perfect by the adaptive modulator; otherwise, explicit consideration of the channel imperfection must be accounted for at the transmitter.